The Influence of Local Culture on Marriage Practices from an Islamic Law Perspective - Maulana Ferdian; Muhamad Anwar; Mhd Ibnu Rizqy S; Khairin Dzaki; Rahmad Fauzi Hasibuan (ISNU Sumatera Utara, 2025)
This study aims to examine local cultural practices in the implementation of marriage in Indonesia and analyze them based on the principles of Islamic law. The approach used is library research by collecting and reviewing various relevant literature on marriage customs in several ethnic groups, such as the practice of forced marriage in the Sasak community in Lombok, elopement (silariang) in the Toraja and Bugis-Makassar tribes, the prohibition of inter-ethnic marriage in Minangkabau, and the tradition of dowry in Bugis culture. The research findings indicate that several of these traditions still conflict with sharia provisions, particularly related to the right to freedom of choice of partner, the principle of justice, and ease in conducting marriage. The practice of forced marriage and elopement that does not meet the requirements of the presence of a guardian and witnesses are considered invalid under Islamic law. Furthermore, the prohibition of inter-ethnic marriage that hinders the implementation of marriage also contradicts Islamic values that emphasize equal rights and justice. The determination of burdensome customary dowries can hinder the goal of a harmonious marriage in Islam. This study emphasizes the importance of integration between cultural customs and sharia through the concept of 'urf sahih so that traditional traditions can be aligned with Islamic teachings. Therefore, the active role of religious and traditional leaders is very necessary in providing education and opening constructive dialogue to correct deviant practices, so that the implementation of marriage can run in accordance with the values of justice, compassion, and humanity according to Islam.